2020
DOI: 10.1016/j.wneu.2020.03.179
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the COVID-19 Outbreak in Northern Italy: Perspectives from the Bergamo Neurosurgery Department

Abstract: W e describe, in this Perspective, the shocking effect of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak on the Department of Neurosurgery of Papa Giovanni XXIII Hospital in Bergamo, which represents at the moment the most affected city in the entire Italian territory (Figure 1). 1 This epidemic is challenging the Italian Government and the health care system and is having a devastating impact on all the health activities, including the neurosurgical reality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
79
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 5 publications
(5 reference statements)
1
79
0
1
Order By: Relevance
“…Although not evaluated in our report, the observed decrease in the number of cases may have been linked to the application of strict guidelines in hospitals and the reorganization of the surgical workforce to enhance front-line health care delivery during the pandemic. [27][28][29] We observed a stabilization in the number of cases per week in the last 3 weeks of our study period (Figure 1). The exact cause of this stabilization late in the course of the pandemic in our report could not be linked to any of the evaluated variables.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Although not evaluated in our report, the observed decrease in the number of cases may have been linked to the application of strict guidelines in hospitals and the reorganization of the surgical workforce to enhance front-line health care delivery during the pandemic. [27][28][29] We observed a stabilization in the number of cases per week in the last 3 weeks of our study period (Figure 1). The exact cause of this stabilization late in the course of the pandemic in our report could not be linked to any of the evaluated variables.…”
Section: Discussionmentioning
confidence: 55%
“…Analysis of current and previous outbreaks has indicated a change in the use of health care services in hospital admissions, outpatient services, and emergency visits. [14][15][16][17][18]27 In a recent survey investigating the effects of the COVID-19 pandemic on 661 neurosurgeons from 96 countries, 21 the overall cancellation rate for elective clinical visits and surgeries reached 57.5% and 51.9% in private and public practice, respectively. The investigators reported that 76% of the cancellations were related to government directions, 14% were related to physician preference, and 7% were related to patient preference.…”
Section: Discussionmentioning
confidence: 99%
“…However, many of the recommendations published by other neurosurgical centers could not be achieved given the local limitations and resources. [1][2][3][4] We believe that systematic pulmonary computed tomography (CT) scan helped initially in assessing a patient's COVID-19 status. 1,5 COVID-19 testing further reinforced the algorithms set up by the local committee and accelerated the diagnosis of suspected cases.…”
Section: Discussionmentioning
confidence: 99%
“…We are now facing a powerful enemy-COVID-19! 1 The consumption of human, material, and financial resources brought about by this campaign should not be underestimated, but we believe that it is controllable. Here, we appeal to all governments and people to join hands to fight against the virus, and we should not expect to get lucky or despise it.…”
mentioning
confidence: 95%